Treatment of Hypertension and Dyslipidemia or Their Combination Among US Managed‐Care Patients - Dutro, Michael P. (J Clin Hypertens (Greenwich), 2007)
The authors examined treatment rates in managed‐care patients with hypertension (HTN) only or dyslipidemia (DYS) only compared with patients who had both (HTN+DYS). A retrospective, cross‐sectional claims analysis was performed in a 2002 US national managed‐care database of 1.23 million continuously eligible members aged 18 years or older. Median age was 44.0 years, 8.8% were aged 65 years or older, and 53.2% were women. Study criteria identified 354,324 patients, 32.9% with HTN only, 34.7% with DYS only, and 32.4% with HTN+DYS. Overall, 49.7% of HTN patients had DYS and 48.3% of DYS patients had HTN. Patients with HTN+DYS were significantly older, more likely to have cardiovascular comorbidities, and more likely to use medications and hospital facilities than were patients with HTN only or DYS only (P<.01). About two‐thirds of patients with HTN only received 1 or more prescription for an antihypertensive medication, compared with three‐quarters of those with HTN+DYS. Fewer than half of patients with DYS only and approximately two‐thirds with HTN+DYS received a cholesterol‐lowering agent.